Baldessin/Whiteley parallel visions - Grishin, Sasha; Wilson, Ashleigh; Baldessin, George 1939-1978; Whiteley, Brett 1939-1992 (National Gallery of Victoria, 2018)
Born forty-two days apart in 1939, Australian artists George Baldessin and Brett Whiteley had much in common. Both were highly innovative artists; both were largely figurative expressionists in their art practices; and both were attracted to the avant-garde, pop culture and existentialism. Tragically, both died young. Baldessin/Whiteley: Parallel Visions features essays exploring aspects of the lives and work of both artists, a rich selection of images and a comprehensive timeline. In following the parallel artistic practices of Baldessin and Whiteley, the publication creates a broader sense of how the work of the two artists ultimately epitomised the times in which they lived. Edited by Sasha Grishin, the book features his lead essay and contributions from Harriet Edquist, Angela Hesson, Katrina Strickland and Ashleigh Wilson